2023
DOI: 10.3390/jcm12185960
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Detection of Bone Tumors around the Knee in X-rays of Children

Sebastian Breden,
Florian Hinterwimmer,
Sarah Consalvo
et al.

Abstract: Even though tumors in children are rare, they cause the second most deaths under the age of 18 years. More often than in other age groups, underage patients suffer from malignancies of the bones, and these mostly occur in the area around the knee. One problem in the treatment is the early detection of bone tumors, especially on X-rays. The rarity and non-specific clinical symptoms further prolong the time to diagnosis. Nevertheless, an early diagnosis is crucial and can facilitate the treatment and therefore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…One illustrative example by Park et al showed ML classification of bone tumors using proximal femur plain radiographs with diagnostic accuracy of 0.853 compared with 0.794 for physicians 39 . Another study by Breden et al reported accuracy of 89.1% in detected radiographic tumors around the knee 41 . This demonstrates the effectiveness of radiographs as they present higher contrast for bony structures facilitating more straightforward feature extraction for ML algorithms.…”
Section: Applications Of Ai In Orthopaedic Oncologymentioning
confidence: 96%
“…One illustrative example by Park et al showed ML classification of bone tumors using proximal femur plain radiographs with diagnostic accuracy of 0.853 compared with 0.794 for physicians 39 . Another study by Breden et al reported accuracy of 89.1% in detected radiographic tumors around the knee 41 . This demonstrates the effectiveness of radiographs as they present higher contrast for bony structures facilitating more straightforward feature extraction for ML algorithms.…”
Section: Applications Of Ai In Orthopaedic Oncologymentioning
confidence: 96%
“…As an emerging machine learning technology, deep learning (DL) has been widely applied to medical image analysis of bone tumors [ 15 17 ], which can distinguish benign and malignant bone tumors [ 11 , 12 , 14 , 18 21 ]. A recent study has highlighted DL’s potential in effectively classifying healthy and pathological X-rays in children [ 22 ]. However, previous studies have primarily focused on the benign and malignant classification of various bone tumors at different sites throughout the body [ 15 , 18 , 21 ], rather than specifically addressing the differential diagnosis of osteolytic OS and GCT around the knee joint.…”
Section: Introductionmentioning
confidence: 99%